CD4+ T cells are required for development of a murine retrovirus- induced immunodeficiency syndrome (MAIDS) (The Rockefeller University Press, 1988)
Mice depleted in vivo of CD4+ Th cells by treatment with mAb GK1.5 were found to be resistant to the lymphoproliferative/immunodeficiency disease (MAIDS) induced in intact mice by infection with the mixture of LP-BM5 murine leukemia viruses. Depleted mice did not develop lymphadenopathy or splenomegaly, had normal serum IgM levels, normal CTL responses to alloantigens, and were able to generate PFC responses to Th-independent antigens even though frequencies of virus-producing spleen cells were comparable in depleted and intact mice. Depletion of CD4+ Th cells after infection resulted in a reversal of many abnormalities exhibited by infected controls; spleen weights, serum IgM levels, and allogeneic CTL responses of treated mice were comparable to those of uninfected controls. These results demonstrate that dysfunction of CD4+ Th cells is central to the induction and progression of both T and B cell abnormalities in MAIDS.